Use of emerging genomic and proteomic technologies in fish physiology - Parrington, J; Coward, K (2002)
The sequencing of the human genome represented a watershed in the biological sciences. Post-genomic biology will be marked not only by vastly greater knowledge about the human genome and those of other species but will see an increasing application of novel and highly sophisticated technologies. Genomic strategies, together with those that look at the proteome of cells and tissues, are likely to revolutionize scientific research over the coming years. The ease with which novel and homologous genes can be isolated using the new databases and technologies, and the ability to study the expression of thousands of genes simultaneously at a global cellular level will be the major factors in this revolution. Genomic information is already being used to further our understanding of physiology and gene evolution in fish. Furthermore, the highly compact pufferfish (Takifugu rubripes) genome is being used extensively as a model to interpret those of tetrapods. Currently, studies of the fish genome are limited to gene evolution and to a much lesser extent, environmental toxicology. However, as interpretation of fish genomes gathers pace, we are likely to see the increasing involvement of other key areas such as reproduction, growth, pathology of disease, and flesh development/quality. Here, we present some of the advanced genomic technologies currently available and discuss how these might influence our knowledge of fish biology. © 2002 Éditions scienfifiques et médicales Elsevier SAS. All rights reserved.